P631 Food triggers in inflammatory bowel disease from the patients' and doctors' perspective. (27th May 2021) - Cappello, M; Guida, L; Di Giorgio, F M; Busacca, A; Carrozza, L; Ciminnisi, S; Almasio, P L
Abstract: Background: Diet is receiving growing attention as a key environmental factor involved in the pathogenesis of Inflammatory Bowel Disease (IBD). Dietary components have a relevant role in triggering symptoms from the patients'perspective, but there is a gap between patients' and doctors' beliefs. Every patient has collected his or her own list of prohibited foods and reports a clinical benefit from avoiding such foods. Elimination of nutrients can lead to nutritional deficiencies and impact on style and quality of life. The aim of this study is to identify frequently avoided foods in a Mediterranean cohort of patients with IBD. Methods: Consecutive patients with IBD attending our tertiary center for infusion of biologics or for follow-up visits were enrolled. Demographics and disease characteristics UC or CD) were recorded in a dedicated database. A questionnaire investigated food avoided and reasons for dietary changes, if self-driven or advised by doctors or other healthcare professionals. Results: 167 patients agreed to participate in the study. Eighty-one patients (48.8%) had UC, 86 (51.5%) had CD. Mean age was 48.6 ± 16 (range 18–77 years), 57.5% were males. Patients were in clinical remission or with mild activity. Most patients, about 80%, and especially patients with CD avoided certain foods considered as triggers, and this avoidance was usually practiced in both exacerbations of the disease and remission periods. This occurred upon medical advice in a minority of patients, especially for vegetable avoidance (13.2%). Foods more frequently avoided were spicy foods, seasoned foods, fried foods, milk and dairy products, carbonated drinks, spirits, vegetables, legumes, and whole grain bread. Processed meat was avoided in about 6.6% (only in 1.8% upon medical advice) and coffee in 12.6%. A lactose-free diet was advised by the treating physicians only in 14.3% of patients. 4 patients were on a glutenfree diet because of a self-reported gluten sensitivity. The role of other healthcare professionals (dietitician, nurses) was marginal in their food choices. Conclusion: Most of the patients set diet on self-experience and give up many foods. Our results are comparable with those of previous studies. Spicy foods, seasoned and fried foods, carbonated drinks, and dairy products are on top of the list. Legumes and vegetables, the cornerstones of the Mediterranean diet, are also avoided even though the evidence that dietary fibers can induce relapse is lacking. The benefit reported could be related to the effect on IBS-related symptoms frequent in IBD in remission. Further studies and a greater involvement of doctors in providing dietary recommendations are warranted.